Clinical and Immunologic Predictors of Mycobacterium avium Complex Immune Reconstitution Inflammatory Syndrome in a Contemporary Cohort of Patients With Human Immunodeficiency Virus. (26th October 2020) - Breglio, Kimberly F; Vinhaes, Caian L; Arriaga, María B; Nason, Martha; Roby, Gregg; Adelsberger, Joseph; Andrade, Bruno B; Sheikh, Virginia; Sereti, Irini
Abstract: Background: People with human immunodeficiency virus (HIV) can present with new or worsening symptoms associated with Mycobacterium avium complex (MAC) infection shortly after antiretroviral therapy (ART) initiation as MAC immune reconstitution inflammatory syndrome (MAC-IRIS). In this study, we assessed the utility of several laboratory tests as predictors of MAC-IRIS. Methods: People with HIV with clinical and histologic and/or microbiologic evidence of MAC-IRIS were identified and followed up to 96 weeks post–ART initiation within a prospective study of 206 ART-naive patients with CD4 <100 cells/µL. Results: Fifteen (7.3%) patients presented with MAC-IRIS within a median interval of 26 days after ART initiation. Patients who developed MAC-IRIS had lower body mass index, lower hemoglobin levels, higher alkaline phosphatase (ALP), and increased CD38 frequency and mean fluorescence intensity on CD8 + T cells at the time of ART initiation compared with non-MAC IRIS patients. A decision tree inference model revealed that stratifying patients based on levels of ALP and D-dimer could predict the likelihood of MAC-IRIS. A binary logistic regression demonstrated that higher levels of ALP at baseline were associated with increased risk of MAC-IRIS development. Conclusions: High ALP levels and increased CD8 + T-cell activation with low CD4 counts at ART initiation should warrant suspicion for subsequent development of MAC-IRIS. Abstract : Clinical and immunologic measurements were tested for prediction of Mycobacterium avium complex (MAC) immune reconstitution inflammatory syndrome in patients with a histologic and/or microbiologic confirmed MAC diagnosis, within a prospective study of 206 ART-naive patients with CD4 counts <100 cells/µL followed up to 96 weeks post–ART initiation.